The Influence of Perception, Motivation, Interest, and Abilities on Students' Decisions Making in Choosing a Human Resource Management Concentration at the University of Riau - Esra Helena Tindaon; Abd. Rasyid Syamsuri; Mida Aprillina Tarigan (Journal of Education Technology Information Social Sciences and Health, 2024)
The purpose of this study to determine the influence of perception, motivation, interest and ability on students' decisions making in choosing a concentration in human resource management at Riau University. This research was conducted at the Management Department, Faculty of Economics and Business, Riau University. The population in this study were management students class of 2020 with a concentration in human resource management, totaling 137 students (secondary data obtained from the Management Department). The sampling technique used in this research is probability sampling, namely simple random sampling which is then calculated using the Slovin formula with a sample of 58 students. The analytical method used in this research is Structural Equation Modeling (SEM) which is processed using SmartPLS 4 and SPSS (Statistical Product Service and Solution) 25. The results of research using hypothesis testing show that perception has a positive and significant effect on decision making. Motivation has a positive and significant effect on decision making. Interest has a positive and significant effect on decision making. Ability has a positive and significant effect on decision making.